Task Performance, Perceived Competence, and Attributed Causes of Performance as Determinants of Intrinsic Motivation - Arnold, Hugh J. (Academy of Management Journal, 1985)
Volunteer subjects engaged in a task that was highly intrinsically motivating under three conditions: no pay, fixed reward, and performance-contingent reward. Results indicated that extrinsic rewards had no effect on either behavioral or self-reported measures of intrinsic motivation, or upon two intervening variables, perceived competence and attributions. As hypothesized, level of task performance was significantly related to perceived competence and attributions, which were in turn significantly related to measures of intrinsic motivation. Locus of control was significantly related to external attribution of the causes of task performance.